2017
DOI: 10.1101/109751
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heterogeneity of normal human breast stem and progenitor cells as revealed by transcriptional profiling

Abstract: During development and pregnancy, the human mammary gland undergoes extensive remodeling in processes driven by populations of stem and progenitor cells. We recently reported that breast cancers are also hierarchically organized and driven by distinct populations of cancer stem cells characterized as CD44 + CD24 low/or by expression of Aldehyde dehydrogenase (ALDH). These sets of markers identify largely non-overlapping mesenchymal and epithelial populations, each of which is capable of tumor initiation when t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…These cells are a heterogenous mix of the various cell types in the breast. Our previous work has shown that these reduction mammoplasty samples contain cells which express the canonical breast stem cell markers ALDH and CD44þ/CD24À (Colacino et al, 2018). In all experiments, cells from each woman were exposed to the various treatment conditions or unexposed as control.…”
Section: Methodsmentioning
confidence: 99%
“…These cells are a heterogenous mix of the various cell types in the breast. Our previous work has shown that these reduction mammoplasty samples contain cells which express the canonical breast stem cell markers ALDH and CD44þ/CD24À (Colacino et al, 2018). In all experiments, cells from each woman were exposed to the various treatment conditions or unexposed as control.…”
Section: Methodsmentioning
confidence: 99%
“…Another study shows that the EMT CSCs characterized by low expression of epithelial specific antigen (ESA), are quiescent, and exhibit lower mitochondrial mass, membrane potential, oxygen consumption, and ROS production as compared to the epithelial CSCs characterized by high ESA expression in several head and neck squamous cell carcinoma (HNSCC) cell lines [ 133 ]. Recently, a subpopulation of normal human breast stem cells (BSCs), exhibiting hybrid ALDH high /CD44 high /CD24 low expression, has been characterized and such ALDH high /CD44 high /CD24 low BSCs have the highest mammosphere formation capacity at the single cell level as compared to apparently more restrictive ALDH high and CD44 high /CD24 low BSCs [ 134 ], hinting that the extent of being stem-like varies among individual subpopulations of stem cells. It seems therefore that the metabolic activities of CSCs at least partially depend on their exact molecular characteristics.…”
Section: Mitochondrial Dependency In Cancer Stemnessmentioning
confidence: 99%
“…Third, since the hybrid metabolic phenotype maintains ROS at a moderate level, cancer cells in the hybrid metabolic phenotype can benefit from moderate ROS-mediated stress response and mutagenic events that stimulate tumorigenesis and metastasis, and avoid the detrimental effects of excessive ROS [ 12 , 35 , 135 ]. Fourth, the hybrid metabolic phenotype may be specifically associated with metastasis [ 9 , 10 , 12 , 90 , 134 ], as discussed before. Fifth, the hybrid phenotype might promote the therapy-resistance of cancer cells.…”
Section: Emergence Of a Hybrid Metabolic Phenotype In Cancer Cellsmentioning
confidence: 99%
“…Besides, Cancer Stem Cell (CSC)-enriched population resides in a hybrid E/M phenotype of triple-negative breast cancer cells [ 73 ]. Last but not least, a subpopulation of normal mammary cells, accompanied by both epithelial-like and mesenchymal-like characteristics, i.e., hybrid E/M phenotype, displays the highest mammosphere-formation capacity [ 74 ]. Thus, a biphasic relationship between stemness and EMT—stemness increases initially during EMT progression, but then subsides as cells complete EMT—seems to be the emerging notion [ 43 , 75 , 76 ].…”
Section: Emt and Stemnessmentioning
confidence: 99%
“…Epithelial-like CSCs, characterized by ALDH high , have higher oxygen consumption rate and lower glycolytic activity compared with the mesenchymal-like breast CSCs, characterized by CD44 high CD24 low [ 98 , 99 ]. Recent work highlighted that ALDH high cells may exhibit a hybrid E/M state [ 74 ]. Future work to analyze the coupled decision-making of metabolism, EMT and stemness needs to be done to comprehensively chart the stable states characterized by varied EMT, stem-like property and metabolism traits, while taking into consideration the direct coupling between gene expression and metabolites, at least partly through epigenetic mechanisms [ 100 ].…”
Section: Metabolic Reprogramming and Emtmentioning
confidence: 99%